A hash-neighborhood-search-network-coding based opportunistic relay retransmission approach - Pengfei SHAO; Yanwei ZHAO; Zhaoxi FANG (Dianxin kexue)
In wireless multicast networks，it is rarely concerned that there may be certain receiving nodes which have better quality links both to the source node and to the other receiving nodes. A novel hash-neighborhoodsearch-network-coding based opportunistic relay retransmission approach was proposed. According to the packet reception status and channel quality，this novel approach dynamically selected the best suitable receiving node whose channel quality was better than the source node as a relay，then hash-neighborhood-search-network-coding strategy was used for the relay to retransmit other receiving nodes’ lost packets. Simulation results show that this novel approach can effectively reduce the number of retransmissions to improve the transmission efficiency with respect to the existing algorithms，especially when one or more of the receiving nodes are interfered and the quality of the channel between receiving nodes and source node continues to decline，this approach can achieve a high retransmission gain.